Upfront BRAF/MEK inhibitors for treatment of high-grade glioma: A case report and review of the literature. Issue 1 (19th November 2022) - Arbour, Gabrielle; Ellezam, Benjamin; Weil, Alexander G; Cayrol, Romain; Vanan, Magimairajan Issai; Coltin, Hallie; Larouche, Valérie; Erker, Craig; Jabado, Nada; Perreault, Sébastien
Abstract: Background: High-grade gliomas (HGG) with BRAF V600E mutation represent a unique subset of central nervous system tumors. Targeted therapies including BRAF and MEK inhibitors are now being explored as possible new treatment options. Methods: We report an 18-year-old female with a grade 3 pleomorphic xanthoastrocytoma treated upfront with dabrafenib and trametinib. We also conducted a systematic literature review of patients with HGG and BRAF V600E mutations treated with BRAF inhibitors. Results: Despite local recurrences resected surgically, the patient has been on dabrafenib and trametinib for more than 54 months. Thirty-two patients with HGG and BRAF V600E mutations treated with BRAF inhibitors were retrieved through our systematic review of the literature. Only 1 young patient with an anaplastic ganglioglioma was treated upfront with a BRAF inhibitor with a curative intent. Best response reported with radiation therapy and systemic therapy was a stable disease (SD) for 18 patients (56.3%) and progressive disease (PD) for 9 patients (28.1%). Responses to treatment regimens that included BRAF inhibitors were reported in 31 patients and included 4 complete responses (12.9%), 23 partial responses (74.2%), 2 SDs (6.5%), and 2 PDs (6.5%). Conclusions: Our patient had durable disease control with dabrafenib and trametinib. Given favorable responses reported in patients with HGG treated with BRAF inhibitors, we believe that upfront targeted therapy is a possible treatment approach that should be studied in the context of a clinical trial.